The effectiveness of training and mentoring in developing ethnomathematicsbased numeracy questions on students' assessment abilities - Maunah Setyawati; Agus Prasetyo Kurniawan; Yuni Arrifadah (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2025)
Mathematics Education students at UIN Sunan Ampel Surabaya, as future mathematics teachers, are required to possess comprehensive competencies to become professional educators. One of these is numeracy competency, which is essential for solving various problems in everyday life. This study aims to describe the effectiveness of training and mentoring in developing ethnomathematics-based numeracy questions among Mathematics Education students, viewed from pedagogical competency standards. Data were collected using tests administered before and after the training and mentoring. The instruments used were test sheets and assessment rubrics to evaluate students’ ability to create ethnomathematics-based numeracy questions based on pedagogical competency standards. The effectiveness of the training and mentoring was determined by analyzing the results of the students’ question development and through statistical analysis using the Paired Sample T-Test. The results showed an increase in the percentage of each indicator of the pedagogical competency standard, and the Paired Sample T-Test obtained a p-value < 0.05, indicating that the development of ethnomathematics-based numeracy questions after training and mentoring was better than before.